Buerger Allen Combination Therapy Exercises and Soak Feet Warm Water Lowers Blood Sugar Levels in Elderly with Diabetes Mellitus Type 2 - Astari Savitri; Diah Ratnawati (Nursing and Health Sciences Journal (NHSJ), 2022)
Management of type 2 diabetes mellitus was needed to overcome the problem of increasing blood glucose levels in the elderly with diabetes mellitus. In addition to pharmacology, there was non-pharmacology as a complementary therapy in reducing blood glucose levels. This study aims to analyze the effectiveness of combined Buerger Allen exercise therapy and feet immersion with warm water for blood glucose levels in the elderly with type 2 diabetes mellitus. The intervention was held 12 times in a period of 15 days with a training schedule three times per week and every day twice at 08.00 WIB and 16.00 WIB with a duration of 16 minutes per meeting. The results of paired T-test were obtained with a p-value is 0,000, indicated there were significant differences in blood glucose levels between before and after therapy. The elderly should go on a Diabetes Mellitus diet, adequate rest, and exercise with combination therapy of burger Allen & soaking the feet in warm water.